Given the equation;
![2x^2-33=39](https://img.qammunity.org/2023/formulas/mathematics/college/b7lv8m0iqsuc8lx96owzlvsrvjyhytz13h.png)
to solve for x;
add 33 to both sides to collect the like terms, we have;
![\begin{gathered} 2x^2-33+33=39+33 \\ 2x^2=72 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/920i8bs48dpftvxbc0wwdkduk9ufyb1vdq.png)
then let's divide both sides by 2;
![\begin{gathered} (2x^2)/(2)=(72)/(2) \\ x^2=36 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6rsc652jcrn8fz4b1amqlflt8iqjipq52f.png)
then to get the value of x, we will square root both sides;
![\begin{gathered} √(x^2)=√(36) \\ x=6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/npsq9auzlx0lzb524tmipio44iwwrvp2pv.png)
from the following equation, we can see that all the steps in the initial solution is right.
to confirm; let us substitute x=6 into the initial equation to see if we will get the corresponding answer;
![\begin{gathered} 2x^2-33 \\ at\text{ x=6} \\ 2x^2-33=2(6)^2-33=72-33=39 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/e2p6bdji7qd2dmln7klm00kwt8aa3i6l0e.png)
This confirms that x=6 is the correct answer.
He made no error.